2023
DOI: 10.1177/15248380221145735
|View full text |Cite
|
Sign up to set email alerts
|

Global Approaches to Primary, Secondary, and Tertiary Elder Abuse Prevention: A Scoping Review

Abstract: Public health professionals use a three-pronged approach to address broad-reaching issues of societal concern: primary prevention, secondary prevention, and tertiary prevention. Applying this framework to the study of elder abuse, the purpose of this review is to describe the status of elder abuse prevention research on a global scale. Elder abuse prevention articles published between 2015 and 2021 were identified through electronic bibliographic searches (PubMed, Medline, CINAHL, APA PsycINFO, and AgeLine). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 77 publications
0
3
0
1
Order By: Relevance
“…Unlike some previous studies [44,45], the present study revealed higher odds of experiencing psychological abuse for the highest income group (OR = 1.28) as well as for older adults who are still working (OR = 1.25). It is noteworthy that the National Elder Mistreatment Study in the United States had previously revealed that relatively younger age (60-69 years vs 70+) and being employed were significant predictors of emotional abuse [46].…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike some previous studies [44,45], the present study revealed higher odds of experiencing psychological abuse for the highest income group (OR = 1.28) as well as for older adults who are still working (OR = 1.25). It is noteworthy that the National Elder Mistreatment Study in the United States had previously revealed that relatively younger age (60-69 years vs 70+) and being employed were significant predictors of emotional abuse [46].…”
Section: Discussioncontrasting
confidence: 99%
“…In recent years, there has been an increased focus on elder abuse as a significant complex social and pervasive health issue (Atkinson & Roberto, 2023; Donnelly & O'Brien, 2022). The awareness of elder abuse and its impact on older people has been gaining attention among researchers, policymakers and the general public worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…A violência interpessoal apresenta maior frequência entre homens idosos do que a autoprovocada (Santos et al, 2022;Lopes et al, 2018a). No entanto, existem muitas falhas na identificação de violência contra o idoso, por exemplo, há poucos relatos e programas de educação e intervenção baseados em evidência e instrumentos validados e culturalmente sensíveis para a identificação de violência em idosos (Atkinson;Roberto, 2024).…”
Section: Principais Características Relacionadas a Violência Interpes...unclassified